The Challenges of Online Learning during Pandemic: Students’ Voice - Irza Yuzulia (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - The global spread of COVID-19 pandemic causes class suspensions resulting in the needs of online learning . Online learning becomes a new challenge for the students and teachers in this pandemic situation. The present research is aimed to investigate the challenges and problems faced by the students during online learning in this covid pandemic situation. The respondents of this research were 54 students in Senior High School. The results showed that the students faced some difficulties in learning online such as poor internet connection, lack of motivation, easily getting distracted and more stressful due to the teachers’ amount of tasks. It is hoped that the teacher can deliver interesting methods and techniques in teaching online to foster students’ motivation and performance in this pandemic situation.Keywords: covid-19, online learning, Students’ perception.Abstrak - Penyebaran global pandemi COVID-19 menyebabkan penangguhan kelas yang mengakibatkan kebutuhan pembelajaran online. Pembelajaran online menjadi tantangan baru bagi siswa dan guru dalam situasi pandemi ini. Penelitian ini bertujuan untuk mengetahui tantangan dan permasalahan yang dihadapi siswa selama pembelajaran online dalam situasi pandemi covid. Responden penelitian ini adalah 54 siswa Sekolah Menengah Atas. Hasil penelitian menunjukkan bahwa siswa menghadapi beberapa kesulitan dalam belajar online seperti koneksi internet yang buruk, motivasi yang berkurang, sulit berkonsentrasi selama pembelajaran online dan menjadi lebih stres karena banyaknya tugas yang diberikan guru. Diharapkan guru dapat menyampaikan metode dan teknik yang menarik dalam pengajaran online untuk menumbuhkan motivasi dan kinerja siswa dalam situasi pandemi ini.Kata kunci: covid-19, pembelajaran online, persepsi siswa.